Coordination polymer chains built from CuII and adipate ions linked by hydrogen bonds to form a three‐dimensional framework structure. Issue 7 (20th June 2014) - Setifi, Zouaoui; Boutebdja, Mehdi; Setifi, Fatima; Merazig, Hocine; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> In the title compound, catena‐poly[bis[(2, 2′‐bipyridine‐κ2N, N′)(1, 1, 3, 3‐tetracyano‐2‐ethoxypropenido‐κN)copper(II)]‐μ4‐hexanedioato‐κ6O1, O1′:O1:O6, O6′:O6], [Cu2(C9H5N4O)2(C6H8O4)(C10H8N2)2]n, the adipate (hexanedioate) dianion lies across a centre of inversion in the space group P<inline-graphic xlink:href="ark:/27927/pghwgd49hf" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. The CuII centre adopts a distorted form of axially elongated (4+2) coordination, and the CuII and adipate components form a one‐dimensional coordination polymer from which the 2, 2′‐bipyridine and 1, 1, 3, 3‐tetracyano‐2‐ethoxypropenide components are pendent, and where each adipate dianion is bonded to four different CuII centres. The coordination polymer chains are linked into a three‐dimensional framework structure by a combination of C—H...N and C—H...O hydrogen bonds, augmented by a π–π stacking interaction.